Outcomes of oncologic arthroplasty in children and adolescents with malignant limb tumors: a systematic review - Vyacheslav I. Zorin; Sergei V. Vissarionov; Alexandr Y. Makarov; Timofey S. Rybinskikh; Kristina N. Rodionova (Travmatologiâ i Ortopediâ Rossii)
Background. Amputation was historically the primary surgical intervention for children with limb bone sarcomas. However, the development and refinement of chemotherapy and radiotherapy protocols, along with advances in surgical techniques and implants, have significantly altered the treatment landscape for these patients. Currently, limb-sparing oncologic arthroplasty is the preferred surgical approach for treating limb sarcomas in children.